Analysis Of Household Consumption Patterns Of Swamp Rice Farmers In Arisan Deras Village Rantau Panjang Sub-District Ogan Ilir District - Kirana, Febriyanti Elngi; Mulyana, Eka (Sriwijaya Journal of Agribusiness and Biometrics in Agriculture Research, 2023)
The agricultural sector is still relied upon by most people as a life support and the main source of income in their households, so it can be referred to as Household Agricultural Business. The rice subsector is the most widely cultivated subsector by Household Agricultural Business in various types of land, one of which is lebak swamp land. Swamp land is a suboptimal land with potential for rice farming. Arisan Deras Village is one of the areas where households depend on rice farming on the swamp land to fulfill their daily needs. The consumption activities of a household will always be different and from this diversity form a consumption pattern. Consumption patterns can be defined as the arrangement of the types and amounts of goods or expenditures resulting from consumption activities carried out by an individual or group to meet their needs. Household consumption expenditure consists of food and non-food consumption. The objectives of this study were (1) to analyze the household consumption pattern of swamp rice farmers in Arisan Deras Village, Rantau Panjang Subdistrict, Ogan Ilir Regency (2) to analyze the factors that influence the household consumption expenditure of swamp rice farmers in Arisan Deras Village Rantau Panjang Subdistrict Ogan Ilir Regency. The research was conducted in May 2023 with a total of 40 farmer households with the criteria that their main livelihood is to be a wetland rice farmer. Data collection methods used survey and interview methods with the help of questionnaires. The results showed that the consumption pattern or consumption expenditure of households of wetland rice farmers in Arisan Deras Village was dominated by food expenditure, with the proportion of food expenditure amounting to 56.08% and the proportion of non-food expenditure amounting to 43.92% each year. Factors that have a significant effect on the consumption expenditure of farmer households are household income and the number of family members, while the level of education of housewives has no significant effect.